Rút gọn các biểu thức sau a, x(2x^2-3)-x^2(5x+1)+x^2 b, 3x(x-2)-5x(1-x)-8(x^2-3)

Question

Rút gọn các biểu thức sau
a, x(2x^2-3)-x^2(5x+1)+x^2
b, 3x(x-2)-5x(1-x)-8(x^2-3)

in progress 0
Athena 2 tuần 2021-07-10T12:23:26+00:00 2 Answers 5 views 0

Answers ( )

    0
    2021-07-10T12:24:26+00:00

    Đáp án + Giải thích các bước giải:

    `a)`

    `x(2x^{2}-3)-x^{2}(5x+1)+x^{2}`

    `=2x^{3}-3x-5x^{3}-x^{2}+x^{2}`

    `=(2x^{3}-5x^{3})+(x^{2}-x^{2})-3x`

    `=-3x^{3}-3x`

    `b)`

    `3x(x-2)-5x(1-x)-8(x^{2}-3)`

    `=3x^{2}-6x-5x+5x^{2}-8x^{2}+24`

    `=(3x^{2}+5x^{2}-8x^{2})-(6x+5x)+24`

    `=-11x+24`

    0
    2021-07-10T12:24:33+00:00

    Rút gọn các biểu thức sau:

    `a)x(2x^2-3)-x^2(5x+1)+x^2`

    `=2x^3-3x-5x^3-x^2+x^2`

    `=(2x^3-5x^3)+(-x^2+x^2)-3x`

    `=-3x^3+0-3x`

    `=-3x^3-3x`

    `b)3x(x-2)-5x(1-x)-8(x^2-3)`

    `=3x^2-6x-5x+5x^2-8x^2+24`

    `=(3x^2+5x^2-8x^2)+(-6x-5x)+24`

    `=-11x+24.`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )